Education on Knowledge of Nutritional Anemia and Determination of Nutritional Status for Santriwati at Darul Istiqomah Islamic Boarding School Sumbersari Jember - Sulistiyani Sulistiyani; Prehatin Trirahayu Ningrum; Ni'mal Baroya (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2022)
Anemia was one of the main problems for female teenagers at this time. Indonesian Basic Helath Research 2018 data showed the prevalence of anemia in female teenager is 32%. Female teenagers, including female students in boarding school, will give birth to the next generation. Therefore, female teenagers must have good nutritional status and be free of anemia. Based on a preliminary survey of 16 female students in the Darul Istiqomah Islamic boarding school, only three female students (18.75%) had good knowledge about anemia. Female students in boarding schools have to know about the impact of anemia. This community service intervention activity aims to increase the knowledge of female students and can determine their nutritional status correctly. The method used in this intervention were counseling and training methods. The result of the bivariate analysis was performed using the Wilcoxon Signed Rank Test with p-value = 0.006 (p < 0.05) so that H0 was rejected. That means there were differences in the level of knowledge of the anemia between before and after the counseling. The female students in boarding school can determine their nutritional status through BMI and upper arm circumference measurement after the training. This activity concludes there are increases in the knowledge between before and after counseling female students. Female students in boarding school can determine BMI and measure the circumference of the upper arm.